Associations between adiposity and physical activity and sedentary behaviour patterns in older women - Zuzana Svozilová; Jana Pelclová; Jana Pechová; Miroslava Přidalová; Izabela Zając-Gawlak; Lenka Tlučáková; Tereza Kaplanová (Palacký University Olomouc, 2019)
Background: Despite broad interest in physical activity (PA) and excessive sitting, it remains unclear what the actual patterns of PA and sedentary behaviour (SB) in older adults are and how they are associated with adiposity. Objective: The aim of this study was to investigate the cross-sectional associations between the total amount and defined bouts of PA and SB with adiposity indicators in older women. Methods: Data on 313 community-dwelling women was used. All women wore an accelerometer for one week and undergone the body composition analysis. We used three adiposity indicators: fat mass percentage (FM%), visceral fat area (VFA), fat mass index (FMI); and the fat-free mass index indicator (FFMI). In multiple linear regression analyses, we adjusted the models for the following confounders: age, wear time, socio-demographic information, smoking, and health status. Results: The mean values of FM%, VFA, FMI, and FFMI were 36.1%, 125.9 cm, 10 kg ⋅ m-2 and 17 kg ⋅ m-2, respectively. Each additional 150 minutes of MVPA per week (regardless of bout length) was associated with a decrease of 3.0% in FM%, 12 cm2 in VFA, and 1.5 kg ⋅ m-2 in FMI. Regarding strong association with bout frequency, doing MVPA lasting ≥ 10 minutes 15 times/week (to meet the target of at least 150 minutes of MVPA/week) would be associated with a decrease of 4.8% in FM%, 24.15 cm2 in VFA, and 2.55 kg ⋅ m-2 in FMI. Significant positive associations for FM%, VFA, and FMI were found with the duration and frequency of sedentary bouts lasting ≥ 20 minutes (β ranging from 0.05-0.42). Conclusions: Significant associations between fat indicators and both PA and SB were found in elderly women. The beneficial associations were much larger for frequency than for duration of bouted MVPA lasting ≥ 10 minutes. The results from this study using SB and PA in terms of total accumulated time and different bouts could be useful for designing interventions for community-dwelling older women.